Motion planning approach for payload swing reduction in tower cranes with double-pendulum effect. Issue 13 (September 2020) - Ouyang, Huimin; Tian, Zheng; Yu, Lili; Zhang, Guangming
Highlights: The jib and trolley positioning and payload sway suppression problems of double-pendulum tower cranes are investigated. The trajectory planning method is presented. The performance of the proposed trajectory is proved by the Lyapunov technique, LaSalle's invariance theorem and Barbalat's lemma. The control performance is demonstrated by comparative simulations. Abstract: Tower crane system is usually considered as single-pendulum system to design controllers. However, in reality, tower crane often exhibits more complex double-pendulum characteristics, which makes it more difficult for positioning and swing angles elimination. To this end, a composite trajectory planning method is designed. The first part of the proposed trajectory guarantees the motion positioning of the jib and trolley, and the second part achieves the purpose of swing suppression by using a damping component. The proposed method can be implemented online that does not need to advance or offline planning. After a series of proof and simulations, it is shown that the proposed method can achieve the desired effect, and at the same time it is robust to uncertain system parameters and external disturbances.